### I am having hard time to understand why a-b = -(b-a)

169

views

0

I just memorize it but I don't quite understand why.

add comment
•
follow this post
modified 10 months ago
by
Andrew Reid
•
written
10 months ago by
Bryan White

### 2 Answers

2

Using the the distributive property,

$-\left(b-a\right)=-1\times\left(b-a\right)=-b+a=a-b$−(`b`−`a`)=−1×(`b`−`a`)=−`b`+`a`=`a`−`b`

add comment
written
10 months ago by
Andrew Reid

0

Intuitively speaking, a-b is the difference between a and b. Whereas b-a is the difference between b and a. They are just opposite of each other and therefore the minus sign.

add comment
written
10 months ago by
Michelle Nelson

Please log in to add an answer/comment or follow this question.